Parasitic Cuscuta factor(s) and the detection by tomato initiates plant defense. Issue 6 (1st November 2016) - Fürst, Ursula; Hegenauer, Volker; Kaiser, Bettina; Körner, Max; Welz, Max; Albert, Markus
ABSTRACT: Dodders ( Cuscuta spp.) are holoparasitic plants that enwind stems of host plants and penetrate those by haustoria to connect to the vascular bundles. Having a broad host plant spectrum, Cuscuta spp infect nearly all dicot plants – only cultivated tomato as one exception is mounting an active defense specifically against C. reflexa . In a recent work we identified a pattern recognition receptor of tomato, "Cuscuta Receptor 1" (CuRe1), which is critical to detect a "Cuscuta factor" (CuF) and initiate defense responses such as the production of ethylene or the generation of reactive oxygen species. CuRe1 also contributes to the tomato resistance against C. reflexa . Here we point to the fact that CuRe1 is not the only relevant component for full tomato resistance but it requires additional defense mechanisms, or receptors, respectively, to totally fend off the parasite.